Antonio Scarpa: an ethnophysician, a doctor-periodeuta, a disease ecologist: Antonio Scarpa - Guerci, Antonio (Medicina Historica, 2020)
Antonio Scarpa can rightly be considered the first ethnomedical practitioner. For 55 years he travelled all over the continents and approached hundreds of ethnic groups curious to learn how they alleviated suffering through the particular practices of their traditional medical systems. During his expeditions, he collected objects, instruments, medicines and iconographic material which are now housed in the museum dedicated to him and donated to the University of Genoa. The result is a precious testimony of a medical knowledge endangered, a historical journey of man in the universe sub specie medicinae. This cultural heritage, together with the activity of Genoese anthropology, led to the establishment of the UNESCO Chair ’Anthropology of Health. Biosphere and care systems’. The challenge of this Chair is to promote encounters between different interpreters of traditions and cultures of care, health and healing, starting from the recognition of cultural diversity.